Cultural Studies Literacy and Numeracy Student Achieving at MAN 2 Kota Bima - Syaifullah; Tasrif; Ida Waluyati; Irman Susanto (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
Study This aim for know studies culture literacy and numeracy student achievement at MAN 2 Kota Bima. The research method used in study This is method study qualitative. Subject study is head school, teacher in charge student achievers, and students’ achievement. Data collection in study This use observation, interviews, and documentation. Based on results research conducted by researchers? so can concluded that, culture literacy and numeracy at MAN 2 Bima City have implemented in a way structured through various coaching programs, creative teacher strategies, as well support adequate facilities. Schools also face? a number of challenges like limitations time and variation interest students, however in a way general capable create environment conducive learning? for support performance student.